2012
DOI: 10.1111/j.1442-2042.2012.02961.x
|View full text |Cite
|
Sign up to set email alerts
|

Carbon‐ion radiation therapy for prostate cancer

Abstract: Abbreviations & Acronyms ADT = androgen deprivation therapy bNED = biological relapse free C-ion RT = carbon-ion radiotherapy CSS = cause-specific survival CT = computed tomography CTV = clinical target volume 3D-CRT = three-dimensional conformal radiation therapy DVH = dose-volume histogram Fr = fractions GHMC = Gunma Heavy Ion Medical Center GI = gastrointestinal GS = Gleason score GU = genitourinary Gy = gray GyE = gray equivalents HAMT = Highly Advanced Medical Technology HDR = high-dose-rate HIMAC = Heavy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
107
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(107 citation statements)
references
References 57 publications
0
107
0
Order By: Relevance
“…Carbon-ion based radiations 1 have been one of the most common cancer therapeutic methods. To improve the therapeutic effect of radiations, sensitizers using nano-materials such as gold nanoparticle, magnetic nanoparticles, and quantum dots have been developed recently 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Carbon-ion based radiations 1 have been one of the most common cancer therapeutic methods. To improve the therapeutic effect of radiations, sensitizers using nano-materials such as gold nanoparticle, magnetic nanoparticles, and quantum dots have been developed recently 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Finally, experience with 12 C ions is promising (typically >83% for all risk groups at 5 years), but limited-only one institution has reported outcomes. [93][94][95][96] Proton beam therapy is the most popular of the particle therapies. Since the 1980s, the early evidence of the benefit of protons was based on simple theories that normal tissues would receive less radiation.…”
Section: Particle Beam Therapymentioning
confidence: 99%
“…Additionally, outcomes in men with intermediate-risk and high-risk prostate cancer have been limited, only reported in a few studies of SBRT 75,76,79 and particle therapies. [87][88][89]91,92,[94][95][96] Finally, many of the studies with newer technologies (particularly SBRT and proton beams) are single-institution experiences, whereas those of conventional therapies are prospective multicentre r andomized trials.…”
Section: Effectivenessmentioning
confidence: 99%
“…Investigators from National Institute of Radiological Sciences, Japan reported their experience in 927 patients treated with hypofractionated conformal carbon-ion radiation therapy between April 2000 and December 2010 [109]. Of 927 patients, 250, 216, and 461 patients were treated with 66 GyE (Gray equivalent (a measure of carbon-ion radiation dose base on an relative biological effectiveness (RBE) ratio of 3 with respect to photon radiation)) in 20 fractions (Fr), 63 GyE in 20 Fr, and 57.…”
Section: Particle Beam Radiation Therapymentioning
confidence: 99%